2012
DOI: 10.1111/j.1752-4571.2012.00238.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic structure and rabies spread potential in raccoons: the role of landscape barriers and sex‐biased dispersal

Abstract: Identifying natural barriers to movements of hosts associated with infectious diseases is essential for developing effective control strategies. Raccoon rabies variant (RRV) is a zoonosis of concern for humans because its main vector, the raccoon (Procyon lotor), is found near residential areas. In Québec, Canada, all cases of RRV found in raccoons since 2006 were detected on the eastern side of the Richelieu River, suggesting that this river acts as a barrier to gene flow and thus the potential for RRV to spr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
47
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(56 citation statements)
references
References 55 publications
6
47
0
Order By: Relevance
“…In comparison with average distances traveled by similar-size mesocarnivores, skunks can be regarded as relatively sedentary [56]. We also predicted that large rivers (physical barriers) and roads (behavioural avoidance and sources of mortality) would limit gene flow in skunks, as previously reported in other mesocarnivores (raccoons [24], [35] and badgers, Meles meles [10]). Finally, we hypothesized that males are more likely to disperse than females and thus, that sex-biased dispersal could be detected indirectly through differences in observed patterns of pairwise genetic relatedness in each sex.…”
Section: Introductionsupporting
confidence: 65%
“…In comparison with average distances traveled by similar-size mesocarnivores, skunks can be regarded as relatively sedentary [56]. We also predicted that large rivers (physical barriers) and roads (behavioural avoidance and sources of mortality) would limit gene flow in skunks, as previously reported in other mesocarnivores (raccoons [24], [35] and badgers, Meles meles [10]). Finally, we hypothesized that males are more likely to disperse than females and thus, that sex-biased dispersal could be detected indirectly through differences in observed patterns of pairwise genetic relatedness in each sex.…”
Section: Introductionsupporting
confidence: 65%
“…Microsatellite polymorphism was assessed at ten loci developed for raccoons (see Côté et al. for the list of loci used and PCR protocols) and at nine loci developed for skunks (see Talbot et al. ).…”
Section: Methodsmentioning
confidence: 99%
“…Previous work in the study area (south‐eastern Québec) has shown very little genetic structuring in resident raccoons and skunks, with highways and rivers generally generating a rather weak effect on patterns of genetic differentiation (Côté et al. ; Talbot et al. ).…”
Section: Introductionmentioning
confidence: 91%
“…Rivers have been shown to impede dispersal and gene flow of a diversity of terrestrial species, including reptiles (lizards: Lamborot et al 2003), birds (Hayes and Sewlal 2004;Voelker et al 2013), and mammals (mustelids: Garroway et al 2011;primates: Ayres and Clutton-Brock 1992;Peres et al 1996). There are also examples of rivers that do not act as barriers (Patton et al 1994;Fairley et al 2002;Lougheed et al 1999;Côté et al 2012). Equivocal support for the riverine barrier hypothesis might be a function of the ecology and dispersal abilities of the focal species in relation to the width and flow rate of the river in question (Haffer 1997).…”
Section: Introductionmentioning
confidence: 97%